Ultrastructural studies of sporulation in Streptomyces. - Hardisson, C (1976)
This is the first study of sporogenesis in Streptomyces carried out on a relatively high number of species (seven) which allows us, using also previously published results, to establish a general picture of this process. In the sporogenesis of Streptomyces two basic stages can be considered: the sporulation septum synthesis and the arthrospore maturation. Our ultrastructural study of the sporulation septum formation suggests the existance within this genus of three basic types. Type I is distinguished because the septum is formed from the beginning by two separate cross walls. Within this type we include Streptomyces erythraeus, Streptomyces albus, and Streptomyces aureofaciens and also include Streptomyces venezuelae, Streptomyces griseus, and Streptomyces osteogriseus. Type II is distinguished because there is a deposit of material previous to the synthesis of the double annulus which completes the septum. This type can be divided into two subtypes. In the first the deposits are wedge-shaped and the double annulus is clearly visible, and to this group belong Streptomyces flaveolus, Streptomyces ambofaciens, and Streptomyces coelicolor. In the second the deposits, which have a different shape and are very well developed, constitute almost entirely the sporulation septum in which the double annulus is barely visible; Streptomyces antibioticus and also Streptomyces viridochromogenes belong to this group. Type III, represented by Streptomyces cinnamonensis, is distinguished because the septum is formed by a single cross wall.